Ciri hidrologi dan hakisan tebing sungai di Sungai Lendu, Alor Gajah Melaka - Mohd Ekhwan Hj. Toriman; Haryati Che’ Lah (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
Hydrological status and river bank erosion were studied in Lendu River catchment, Melaka. Data obtained from Batu Berendam climatological station was used to analysed hydrological status at the study area. Bank erosion measurement was also carried out using erosion pin technique. Data then were analysed using Smith’s simple statistics. Results from hydrological analyses reveal that Lendu River is classified as L3W1 hydrological region with Precipitation (P) – Potential Evapotranspiration (PE) is below 500 mm per annum. Meanwhile, potential runoff was estimated at 466 mm and average rainfall for a period from 1970 to 2002 was calculated at 1999 mm, a value below the national average for Peninsular Malaysia. The months of September, October and November received maximum rainfall at 208 mm, 205 mm and 242 mm, respectively. Using Thronwaithe’s equation, the minimum and maximum potential evapotranspiration occurred in November (119 mm) and February (136 mm). Using the erosion pin technique, highest erosion was recorded at Plot 1 (78.84 cm), followed by Plot 3 (43.5 cm) and Plot 2 (30.36 cm). Overall, total erosion recorded over the study period was 152.4 cm- an average of 30.4 cm per month or 3.65m year-1. Analysis using Smith’s simple regression showed that rainfall and river discharge are the most significant parameters in influencing river bank erosion. The construction of river bank structure is an alternative to control river bank erosion in Lendu River. However, this approach needs regular maintenance particularly during the flood events